Ismail Gasprisky's Travels to Bukhara (American Journal of Public Diplomacy and International Studies (2993-2157), 2024)
This article describes the difficult life path of Ismail Gasprinsky, one of the last thinkers of the Turkic world in the 19th century, the way to implement his progressive and life-giving ideas aimed at uniting the nations and peoples that were torn apart during the years of colonialism. dedicated to the description of the modern schools opened in Bukhara as a result of his incomparable efforts and the methods of teaching in them.